Use of beta‐blocker is associated with lower mortality in patients with coronary artery disease with or without COPD. (4th November 2018) - Rezaei, Safoura Sheikh; Rinner, Christoph; Ratajczak, Paulina; Grossmann, Wilfried; Gall, Walter; Wolzt, Michael
Abstract: Introduction: Beta‐blockers are indicated for secondary prevention of coronary artery disease (CAD). However, in patients with co‐morbidity of chronic obstructive pulmonary disease (COPD) an underuse of beta‐blocker has been reported. Materials and Methods: Prescription and demographic data and information on hospital discharge diagnoses from 13 Austrian health insurance funds for the years 2006‐2007 were analyzed. The primary end point was all‐cause mortality of patients with CAD with or without COPD and its association with use of beta‐blockers. Results: In 2006 and 2007, 65717 patients (37% female, 63% male) were discharged with a diagnosis of CAD. Among these patients, 46% had a co‐diagnosis of COPD, 24% had diabetes, and 75% received beta‐blockers. Use of beta‐blockers was comparable in CAD patients with COPD and without COPD with 77% and 74%, respectively. Thousand eight hundred seventy‐two (8.1%) and 1473 (5.6%) patients with and without COPD, who used beta‐blockers died within months in 2006 and 2007. Thousand five hundred fifty‐three (22.0%) and 1862 (22.2%) of patients with and without COPD and without beta‐blockers died during the corresponding time period. Discussion: Use of beta‐blockers was similar in patients with CAD with or without co‐diagnosis of COPD. However, mortality of beta‐blocker users was markedly lower than that of nonusers in patients with CAD with or without COPD.